(3QhVI GdYbdGA (B((3hfRgI GdaVdGA(B)s - (3eMeO Hf MHGf Hf CMeO Hf MHGf Hf eYGP Hf eYHO GdJejej, CHh MGJe GdHSJj, hjbGd dg GHf MHGf,J (B354 (3g` s ((3MQGf s)
(3ChdgG (B:s
(3CeG HYO aEf GdReGf bO jJHfi dYGbd JZjQg , hdGM ddHjH JHOdg afHY ajg CbhGe jOYhf GdYbd HGSJYeGdg VO eG jhLH GdYbd ef TghGJ UOhQge s
(3BNQgG (B:s
(3WdH GdhUhd Edi eMd Cgd hdGjJg Efg efJgi GdZGjI YfO QLGA GdeDefjf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B52 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B928s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs